1994
DOI: 10.1111/j.1365-2869.1994.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma insulin and lipid levels in untreated obstructive sleep apnoea and snoring; their comparison with matched controls and response to treatment

Abstract: Obstructive sleep apnoea (OSA), and snoring are associated with coronary heart disease. To assess whether OSA or snoring may contribute to this by raising fasting lipid or insulin levels, venous fasting total cholesterol, triglyceride, very-low-density lipoprotein, low-density lipoprotein, high-density lipoprotein, and insulin were measured in 15 untreated OSA patients and 18 snorers. Each of these subjects was individually matched to a control of the same sex, age +/- 10%, body index +/- 15%, smoking and drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 21 publications
2
61
0
1
Order By: Relevance
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 64%
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 64%
“…In contrast, two other controlled studies suggested that the relation between sleep apnea and plasma insulin levels (4) or insulin resistance (5) reflected the known effects of obesity. However, in one of these studies the apneics were otherwise healthy normotensive individuals (5), whereas in the second one they were lean and less symptomatic than our patients (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the potential independent role of sleep apnea in the development of insulin resistance and/or vice versa have been inconsistent and inconclusive. Recent studies suggested that the effects of sleep apnea on insulin dynamics and effects could be accounted for completely by obesity (4,5).…”
mentioning
confidence: 99%
“…In contrast, two other controlled studies suggested that the relation between sleep apnea and plasma insulin levels (63) or insulin resistance (64) reflected the known effects of obesity. However, in one of these studies, the apneics were otherwise healthy normotensive individuals (64), whereas in the second one, the apneics were lean and less symptomatic (63). The weak correlations between sleep apnea and insulin levels in clinical samples and the absence of insulin resistance in otherwise asymptomatic apneics reported in some studies may be due to the possibility that sleep apnea is a heterogeneous disorder in terms of its association with insulin resistance and/or that sleep apnea without symptoms has a weak association with insulin resistance.…”
Section: Sleep Apnea and Insulin Resistancementioning
confidence: 99%